Active films based on thermoplastic corn starch and chitosan oligomer for food packaging applications - Castillo, Luciana A. (2017)
Antimicrobial biodegradable films based on thermoplastic corn starch (TPS) and chitosan oligomers (CO) were obtained in order to develop a package prototype for perishable food products. Active films were fabricated thermo-compressing a sandwiched structure constituted by a thin layer of an oligomers enriched solution between two TPS films, previously made by melt-mixing and hot-pressing. Regarding enriched solution, it was obtained by dissolving oligomers in diluted acetic acid. Final material was characterized, determining its physical and optical properties, as well as, studying its microstructure. By diffusion assays it was demonstrated the capability of CO to migrate from the active film towards the aqueous simulant media. Moreover, oligomers were able to diffuse from the matrix, regardless the aqueous medium acidity. Experimental data of diffusion assays were fitted using a mathematical model, estimating diffusion coefficients at three studied pH values (3, 5, and 7). Active film was used to obtain sachets to package perishable foods such as strawberries, ricotta, and flavored breads, which were stored for 7 days under controlled conditions. Antimicrobial capacity of active sachets was corroborated through molds and yeast counts in the stored food products. Additionally, it was demonstrated that CO incorporation to the packaging material resulted in a more efficient way to inhibit microbial development than the spraying technique.